PENGARUH KOMBINASI TAKARAN PUPUK UREA DAN SP-36 TERHADAP PERTUMBUHAN DAN HASIL BAWANG DAUN (Allium fistulosum L.) - Amran Jaenudin; Adib Nahdudin (Agroswagati Jurnal Agronomi, 2014)
The  objective  of  the  research  is  to  knowthe effects of the combination of Urea Fertilizer and SP-36 on growth and yield of onion (Allium fistulosum L.) and to determine dose combination of urea and SP-36 best effect, on growth and yield of onion (Allium fistulosum L.). The study was conducted from July to September 2013. The method used to experimental method with a Randomized Block Design (RBD) consists of two factors, namely urea and SP-36. Combination treatments with as much as 9 combination treatments was repeated 3 times, so there are 27 experimental units. Implementation of research activities include land preparation, seed preparation, planting, maintenance, and harvesting. Observed variables, namely : plant height (cm), number of leaves (pieces), number of tillers (fruit), fresh weight per clump (g), fresh weight per plot (kg), nett weight per clump (g), and the nett weight per plot (kg). Treatments dose the combination of Urea 300 kg/ha and SP-36 300 kg/ha, which shows real results, the highest number of tillers with an average 6.0 age 56 (Day After Plant), fresh weight of 137.0 g per clump, fresh weight of 6.14 kg per plot age 60 (Day After Plant), the nett weight of 132.0 g per clump, and the nett weight of 6.06 kg per plot age 60 (Day After Plant).The  objective  of  the  research  is  to  knowthe effects of the combination of Urea Fertilizer and SP-36 on growth and yield of onion (Allium fistulosum L.) and to determine dose combination of urea and SP-36 best effect, on growth and yield of onion (Allium fistulosum L.). The study was conducted from July to September 2013. The method used to experimental method with a Randomized Block Design (RBD) consists of two factors, namely urea and SP-36. Combination treatments with as much as 9 combination treatments was repeated 3 times, so there are 27 experimental units. Implementation of research activities include land preparation, seed preparation, planting, maintenance, and harvesting. Observed variables, namely : plant height (cm), number of leaves (pieces), number of tillers (fruit), fresh weight per clump (g), fresh weight per plot (kg), nett weight per clump (g), and the nett weight per plot (kg). Treatments dose the combination of Urea 300 kg/ha and SP-36 300 kg/ha, which shows real results, the highest number of tillers with an average 6.0 age 56 (Day After Plant), fresh weight of 137.0 g per clump, fresh weight of 6.14 kg per plot age 60 (Day After Plant), the nett weight of 132.0 g per clump, and the nett weight of 6.06 kg per plot age 60 (Day After Plant).